Hepatoprotective Potential of Apigenin versus Vitexin: A Comparative Study in an Acetaminophen-Induced Acute Liver Injury Rat’s Model - Shaymaa Fadhil Abbas; Sarah Adil Haji; Raad Saad Luty (Iraqi Journal of Pharmaceutical Sciences, 2026)
Background: Paracetamol poisoning is a global issue that results in severe liver failure and permanent liver damage, necessitating the need for liver transplantation. The objective of our study was to assess and compare the preventive effects of Apigenin and vitexin against paracetamol-induced liver damage in rats. Methods: Rats were divided into four groups and treated for seven consecutive days. Group I received 0.5% DMSO, Group II received a single paracetamol dose, and Groups III-IV received 10 mg/kg Apigenin or 40 mg/kg vitexin i.p for 7 days. On the seventh day, all groups except the Group I received a single oral dosage of 3000 mg/kg paracetamol three hours after their final Apigenin or vitexin dose. After 24 hours of paracetamol administration, the animals were sacrificed and their blood and livers were taken for biochemical and histopathological examination. Results: The results demonstrated that paracetamol treatment led to notable increases (p < 0.05) in blood biochemical markers (ALT, AST, and ALP), in contrast to the negative control groups. However, after receiving Apigenin, rats exhibited a notable decrease (p<0.05) in the level of these biomarkers. After vitexin pretreatment, the levels of these enzymes were reduced, but this reduction was statistically significant only for the ALP level when compared to the paracetamol group. (p<0.05). Furthermore, Apigenin pretreatment was able to restore normal liver histopathology, while vitexin was not. Conclusion: our research validated the hepatoprotective properties of Apigenin against paracetamol hepatotoxicity and provided insight into potential distinctions in the effects of a flavonoid and its glycosylated form.